当m-n=5(m+n)时,求【6(m-n)/m+n】-【5(m+n)/m-n】的值
2个回答
由于m-n=5(m+n)
(m-n)/m+n=1/5
(m+n)/m-n=5
【6(m-n)/m+n】-【5(m+n)/m-n】=6/5-5*5=-23.8
相关问题
当m=99.5,n=49.5时,求(m/m+n)平方-(n/m+n)平方的值
已知N+N+N+M+M=6.4,N+N+M+M=5.6求M-N=?M+N=?算出数字
已知2m-5n=0,求(1+n/m-m/m-n)/(1-n/m-m/m+n)的值
已知2m-5n=0,求(1+(n/m)-(n/m-n))除以(1-(n/m)-(m/m+n))的值
当m=4,n=-5时,求代数式2/3(2m-n)-2(4n-m)+(-3/4)(m+n)的值
已知2m-5n=0,求值:(1+n/m-m/m-n)÷(1-n/m-m/m+n)
(m-5n)(m-n)-6(m+2n)(m-3n)
已知m+n=7,mn=-5,求(m-n)(n-m)+(2m-n)+(m-2n)的值.
已知m/n=5/3 求(1/m+n+1/m-n)÷1/n-n/m-n÷m+n/n的值,
m/n=5/3,求(m/m+n)+(m/m+n)-(n^2/m^2-n^2)